The legal implications of economic partnership agreements on regional integration in East and Southern African - Musoni, Ronald (Centre for Law and Society, 2026)
The European Union is currently negotiating new trade agreements in the form of -Economic Partnership Agreements (EP As) with members of its former colonies- the African, Caribbean and Pacific (ACP) Countries. According to the European Commission's directorate general for trade, such agreements contain provisions aimed at progressively removing trade barriers, enhancing cooperation in trade related areas and fostering regional development. However juxtaposed against the endeavors of the regional integration efforts already established, especially in East and Southern Africa, the question one can't help but ask, is whether these EPAs will support the existing efforts at regional integration? This study therefore examined the legal implications of these EP As on the regional integrations efforts already established in the East and Southern African regional economic communities (RECs). This necessitated critical discussion on controversial clauses of the EP As and issues raised during the negotiations of the EP As, such as the reconfiguration of the membership of the various members of the RECs, the definition of parties to the agreement, and the inclusion of non-trade issues in the EPA agreements. The study established that EP As, in their current form, have the potential to hamper regional • integration in the RECs. Such agreements demands for the reconfiguration of membership in the various RECs are not geared at promoting the integration process of these communities into the world economy that is based on their initiatives (RECs'). It would seem, rather, that the EP As are tailored to serve only the interests of the EU. The study therefore concluded by offering solutions that would alleviate the potentially detrimental effects of EP As on the regional integration processes in East and Southern Africa which are geared towards integration into regional economic blocs.